Oxford handbook of emergency nursing - Crouch, Robert, OBE; Charters, Alan; Dawood, Mary; Bennett, Paula ([Oxford] : Oxford University Press, 2016)
This handbook provides guidance on the particular issues faced by emergency nurses. Taking a systems-based approach, practical guidance is given on common and rarer occurrences encountered in the emergency setting. Immediate management, investigations, onward referral and practical skills are covered in a succinct format.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 13, 2016).
Keywords: Emergency nursing